Technological Determination on Digital Mass Media Consumption in Marginalized Communities - Endah Nursamsi, Sari; Astuti, Hanny; Husni Mubarok, Muhamad; Reza Gusti Safitri, Islamu; Raja Neesha, Azzuri (Siber Journal of Advanced Multidisciplinary, 2024)
Purpose – The research aims to observe the preferences and decisions regarding the consumption of digital mass media within marginalized communities and the adaptation process of communities concerning digital communication technology. Design/methodology/approach – This research is a qualitative approach, specifically using the phenomenological method. The primary data is collected through observations while interviews used as secondary data. Subsequently, all the data is carefully selected, processed, and analyzed within the framework of technological determinism theory. Findings – Lower-cost cellular and Android devices offer a potential solution to accessibility barriers in the market, despite their minimal quality. However, significant challenges persist, including knowledge gaps, technological inadequacies, and limited digital literacy skills become obstacles to broader technological usage. Research limitations/implications – This study specifically targets marginalized communities in Bekasi, recognizing their restricted digital access and reliance on fishing as a livelihood. However, it does not extend its scope to encompass marginalized groups across Indonesia as a whole. Practical implications – The results obviously offer ideas in practical digital media literacy for similar communities and government to improve community capabilities in consuming media information. Originality/value – this research contributes the digital media literacy formula and encourages the pursuit digital technology for marginal community, through consumption of good news.